Tax incentives and the choice of organisational form of small businesses: Identification through a differentiated payroll tax schedule - Andrea Papini (University of Essex, Institute for Social and Economic Research (ISER), 2018)
The Norwegian dual income tax system gave incentives for business owners to incorporate and take advantage of the lower tax on capital income. The tax reform of 2006, which was designed to eliminate these incentives, is used to discuss effects of taxation on the choice of organisational form. The interplay between the tax reform and the pre-existing system of geographically differentiated payroll tax rates generates heterogeneity in the tax treatment, which is exploited in a difference-in-differences empirical strategy. Estimation results based on a large administrative dataset suggest that organisational choice is influenced by taxes: a 1 percentage point reduction in the payroll tax results in 1 percent increase in incorporation rate.
Keywords: H25; L22; 330; Business taxation; Organisational form; Small businesses